2018
DOI: 10.1039/c8ra08433e
|View full text |Cite
|
Sign up to set email alerts
|

Novozym 40086 as a novel biocatalyst to improve benzyl cinnamate synthesis

Abstract: Novozym 40086 was used as a novel biocatalyst to improve benzyl cinnamate synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…Wang et al [ 9 ], used 30 mg.mL −1 of Lipozyme TL IM lipase, solvent isooctane, and the same molar ratio and temperature reported by Zhang et al [ 18 ] during 24 h of reaction. Sun and Tian [ 19 ] were able to reduce the amount of Novozym 40086 lipase to 20 mg.mL −1 and reaction time to 11.3 h. In our study, it was possible to reduce the amount of biocatalyst 5 times when compared with Sun and Tian [ 19 ]. This is an important factor to be considered, since enzymes have a high commercial value, and their reduction can considerably decrease the cost of the process.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [ 9 ], used 30 mg.mL −1 of Lipozyme TL IM lipase, solvent isooctane, and the same molar ratio and temperature reported by Zhang et al [ 18 ] during 24 h of reaction. Sun and Tian [ 19 ] were able to reduce the amount of Novozym 40086 lipase to 20 mg.mL −1 and reaction time to 11.3 h. In our study, it was possible to reduce the amount of biocatalyst 5 times when compared with Sun and Tian [ 19 ]. This is an important factor to be considered, since enzymes have a high commercial value, and their reduction can considerably decrease the cost of the process.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous reports, some catalysts were used to prepare alkyl caffeate by transesterification or esterification. 14–17 Chen et al 15 and Xiao et al 18 synthesized octyl caffeate using Novozym 435 (2000$ per kg) in an isooctane system for a long time (>52 h). Pang et al 14 reported chemoenzymatic synthesis of propyl caffeate using lipase-catalyzed the transesterification of 1-propanol and intermediate (methyl caffeate).…”
Section: Introductionmentioning
confidence: 99%
“…They are usually employed to catalyze a stereoselective esterification or transesterification reaction of the alcohol substrate 12–14 . Novozym 40086 (lipase from Rhizomucor miehei immobilized on acrylic resin beads) is a new commercial immobilized lipase and provides an efficient biocatalyst for kinetic resolution of secondary aromatic alcohols 15 . In this paper, Novozym 40086 catalyzed transesterification of 1‐(4‐methoxyphenyl)ethanol (MOPE), a widely used secondary aromatic alcohol, in organic solvent was investigated to resolve the MOPE enantiomers with good stereoselectivity and activity.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Novozym 40086 (lipase from Rhizomucor miehei immobilized on acrylic resin beads) is a new commercial immobilized lipase and provides an efficient biocatalyst for kinetic resolution of secondary aromatic alcohols. 15 In this paper, Novozym 40086 catalyzed transesterification of 1-(4-methoxyphenyl)ethanol (MOPE), a widely used secondary aromatic alcohol, in organic solvent was investigated to resolve the MOPE enantiomers with good stereoselectivity and activity. The effects of a series of important factors were studied and the reaction conditions were optimized.…”
Section: Introductionmentioning
confidence: 99%